The Psychology of Tail Events: Progress and Challenges - Barberis, Nicholas (American Economic Review, 2013)
Over the past decade there has been a surge of interest in “tail events,” or rare, high-impact events. In this article, I start by summarizing some recent progress in our understanding of the psychology of tail events. I suggest that much of this progress has centered on the concept of “probability weighting” and, in particular, on applications of this concept in various fields of economics. I then describe some major open questions in this area.